Uji Efek Stimulansia Ekstrak Etil Asetat Kulit Kayu Akway (Drymis piperita) Asal Papua Pada Tikus (Ratus norvegicus) Jantan - Rani D. Pratiwi; Eva S. Simaremare (Jurnal Biologi Papua, 2020)
Drymis sp. stem bark from Papua widely utilized by local people especially in Sougb Tribe from Sururey Distric Pegunungan Arfak West Papua, one of them is used to increase the stamina of the body. The aim of this study was to investigate the tonic effect of Drymis sp. stem bark of Ratus norvegicus. Ratatory exhaustion method was used to the tonic effect. Selected rats (30) were divided into 6 groups, each consisting of 5 rats. Tested extract was administrated oraly one dose to the rats. Group I, II and III was given the ethil acetat fraction of Drymis sp. stem bark 10mg/kg body weight, 30mg/kg body weight and 50mg/kg body weight consecutively. Group IV was given CMC-Na 0,5% (as negative control). Goup V was given caffein 15 mg/kg body weight (as positive control) and Group VI as a control. The total swimming period until exhaustion was measured and use as index of swimming capacity. Research result show that the highest dose 50 mg/body weight of the tested fraction the longer swimming time and with better stamina. The result of One Way ANOVA test showed that there was a significant difference between treatment group, followed by tukey test, tukey result obtained the ethil acetat fraction and negative control (CMC Na) showed that there was significant difference, and there is no real difference between between treatment group and positive control.   Key words: Drymis sp, Papua, tonic effect, rats.